2009
DOI: 10.1111/j.1469-8749.2008.03181.x
|View full text |Cite
|
Sign up to set email alerts
|

Movement disorders associated with complex regional pain syndrome in children

Abstract: The aim of the present study was to review the history, clinical course, treatment, and outcome of movement disorders in children and young people with complex regional pain syndrome (CRPS). Case notes were reviewed retrospectively of children and young people who presented with movement disorders in CRPS to our tertiary paediatric pain service over a period of 13 years. Ten children with CRPS presented with movement disorders (eight females, two males). The age at first presentation with symptoms of CRPS rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
(30 reference statements)
0
17
0
Order By: Relevance
“…In a study of 32 children with CRPS attending a paediatric service in the UK over 10 years, 10 patients (30%) also had dystonia 19. It is estimated that 25% of adult patients with CRPS also suffer from movement disorders mostly (20%) dystonia 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 32 children with CRPS attending a paediatric service in the UK over 10 years, 10 patients (30%) also had dystonia 19. It is estimated that 25% of adult patients with CRPS also suffer from movement disorders mostly (20%) dystonia 26…”
Section: Discussionmentioning
confidence: 99%
“…A history of injury is almost always demonstrated in affected children and the lower limbs are more often affected than the upper limbs, while the upper extremity was affected more frequently than the lower extremity in adults. Abnormal movements and dystonia have also been frequently reported in adults and children with CRPS and may complicate the clinical picture 19 20…”
Section: Introductionmentioning
confidence: 99%
“…A larger study with 692 CRPS-I patients found 124 (19.9%) cases of dystonia (de Boerl et al, 2011). In paediatric population, dystonia is as well the most common movement disorder (Agrawal et al, 2009). Verdugo and Ochoa (2000) assessed 58 CRPS patients, of which only CRPS-I and not CRPS-II patients presented with combinations of dystonic spasms, coarse postural or action tremor and irregular jerks.…”
Section: Clinical Findings Linking Crps To Basal Ganglia Dysfunctionmentioning
confidence: 99%
“…Physical therapy alone was reported to be highly effective many years ago [42]: many clinicians, however, find a significant proportion of children are unable to participate fully, due to pain, and require a multidisciplinary approach. Movement disorders are increasingly recognized in CRPS and can be very difficult to manage [43 ]. Multicentre trials for the management of CRPS in children are needed.…”
Section: Neuropathic Painmentioning
confidence: 99%